Syntactical Error Analysis on Conjunctional Students’ English Narrative Composition - Andi Santoso; Muhammad Rinzat Iriyansah (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2020)
The aims of this research are to know the errors made by the learners on their English narrative composition; to identify the factors made the errors by learners; to identify the errors made by the learners; to correct the errors which have been made; to improve the teaching quality appropriating the curriculum and the syllabus; as well as to get the data and the explanation about the difficulties in studying English especially in arranging the conjunction of English narrative composition. The method used in this research is descriptive method that gives the data and the explanation about the recent symptoms of the errors made by the learners. The descriptive method consists of the ways in giving the note, the analysis and the interpretation about the recent condition. The characteristic of the descriptive method is to give the existence of the data which is straight to the problems as the recent variables are not manipulated. The research was carried out by conducting a written test of English narrative composition for the learners. After analyzing the data, the findings point out that the errors of coordinate conjunction are 33.3% and the subordinate conjunction is 66,7 %. Keywords: syntactical error, conjunctional, narrative text